PIC BASED CONTROLLER AREA NETWORK (CAN) - SHAFEI, AZHANI AHMAD (Universiti Teknologi PETRONAS, 2007)
The field of automation and control is constantly expanding and with that the complexity in automation and control system has also been increasing. The complexity ofcontrol systems and the need toexchange data between them mean that moreand morehard-wired, dedicated signal lineshaveto be provided. The challenges faced in automation and control system is thecomplexity of wiring, thecomplexity of the system itself and its reliability in harsh environment. Controller Area Network (CAN) provides solution in dealing with complexity of networking. CAN is also growing in popularity due to its ease of use and low costs in implementing them. CAN is as simple to use as a serial UART, and currently the cost ofCAN controllers is still decreasing. The implementation of CAN not only covers the car and automation industries, but also into fields such as medical instrumentation and domestic appliances. One ofthe CAN microcontrollers available inthe market isthe Microchip's PIC18 family. The project's goal is to set up Controller Area Network (CAN) by utilizing the Microchip's PIC18. Microchip's MCP2551 CAN transceivers are used to interface the CAN controllers with the CANbus. C language program is writtento controlthe microcontrollers. TheC program is translated to HEXfile using CCS compiler. The HEX files are downloaded onto the microcontrollers. The traffic of the transmission of the messages is monitored using HyperTerminal. The microcontrollers are able to send messages among them using the CANmodule. The ID ofthe message transmitted from one microcontroller matches the ID received from the receiving microcontroller. This work demonstrates a CAN network built using PIC microcontrollers.